A low-temperature, high-impact ternary copolymer polypropylene modified material and its preparation method

CN122941101APending Publication Date: 2026-10-20RUIAN JUNCHENG PLASTIC MFG CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611434636.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种低温高冲击三元共聚聚丙烯改性材料及其制备方法,以解决上述背景技术中提出三元共聚聚丙烯低温增韧体系为达到低温冲击要求通常需添加较高比例的弹性体,导致弯曲模量和热变形温度明显下降,刚性与韧性难以兼顾,游离型β晶型成核剂在熔融共混过程中随机分散于聚丙烯连续相中,无法定向富集于聚丙烯/弹性体相界面的应力集中区域,且易发生团聚和迁移,成核效率低、稳定性差,并且单一粒径的弹性分散相难以同时兼顾微裂纹萌生的抑制与裂纹扩展的阻断,无法在冲击载荷升高过程中形成分级耗能机制的问题

Benefits of technology

该低温高冲击三元共聚聚丙烯改性材料及其制备方法,通过化学键将β晶型成核基团固定于马来酸酐接枝OBC链段,降低自由成核剂在连续相内随机成核和团聚的比例,使成核功能更集中地作用于弹性体相界面;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a low-temperature, high-impact ternary copolymer polypropylene modified material and its preparation method, relating to the field of new polymer materials. The material comprises, by weight, 70-82 parts of ternary copolymer polypropylene; 6-12 parts of ethylene-octene block copolymer; 3-8 parts of propylene-based elastomer; 3-7 parts of interface crystallization toughening masterbatch; 0.2-0.6 parts of antioxidant; 0.1-0.5 parts of lubricant; and 0.05-0.2 parts of acid absorbent. This low-temperature, high-impact ternary copolymer polypropylene modified material and its preparation method fix β-crystal nucleating groups to maleic anhydride-grafted OBC segments through chemical bonds, reducing the proportion of random nucleation and aggregation of free nucleating agents within the continuous phase, allowing the nucleation function to act more concentratedly on the elastomer phase interface. The β-crystal-rich region near the interface has lower crystal density and higher plastic deformation capacity, which can mitigate the modulus abrupt change between the continuous polypropylene phase and the elastic phase, improve stress transfer stability, and promote shear yielding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new polymer materials technology, specifically to a low-temperature high-impact ternary copolymer polypropylene modified material and its preparation method. Background Technology

[0002] Polypropylene, as one of the general-purpose plastics, is widely used in automotive parts, medical devices and electronic appliances due to its outstanding advantages such as low density, good chemical corrosion resistance, excellent electrical insulation, excellent processing performance and low cost. However, with the rapid development of strategic emerging industries such as new energy vehicles, high-end equipment manufacturing and precision electronics, the development of new polypropylene materials with high rigidity and excellent low-temperature impact resistance has become an important research direction in the field of new polymer materials. For example, the patent for automotive polypropylene-ethylene propylene diene monomer (EPDM) modified composite material with announcement number CN111073146A includes the following raw materials in parts by weight: 70-80 parts polypropylene, 70-80 parts EPDM, 10-15 parts modified glass fiber, 10-15 parts mica powder, 10-15 parts polyethylene glycol, 1-2 parts zinc stearate, and 1-2 parts additives. The modified composite material uses polypropylene and EPDM as the main raw materials, with the addition of modified glass fiber to improve the overall impact resistance of the composite material. At the same time, the addition of mica powder improves the overall strength and heat resistance of the composite material. For example, patent CN105694228A discloses a polypropylene-modified ternary composite material for plastic geogrids, which is composed of the following raw materials by weight percentage: 10%–30% recycled polypropylene; 5%–15% glass fiber; and the remainder is polypropylene-specific material. In the production process of geogrids, the addition of recycled or recycled polypropylene reduces production investment costs, saves resources, and reduces environmental pollution. However, it will have a certain negative impact on the mechanical properties of the product. Therefore, improving the mechanical properties of geogrid materials through material modification methods to meet practical application requirements while reducing costs has certain theoretical significance and application value. The steps are simple, the operation is convenient, and the practicality is strong. For example, patent CN119661943B discloses a modified polypropylene material, its preparation method, and its application. The modified polypropylene material, by weight, comprises the following components: 35-75 parts polypropylene, 20-30 parts ethylene-propylene-butadiene terpolymer polypropylene, 15-25 parts talc, 2-27 parts elastomer, and 0.2-6 parts additives. The polypropylene includes high molecular weight copolymer polypropylene and low molecular weight homopolymer polypropylene in a weight ratio of 1:(0.1-1.6). The weight-average molecular weight of the high molecular weight copolymer polypropylene is (250,000-400,000), and the weight-average molecular weight of the low molecular weight homopolymer polypropylene is (100,000-260,000). Most of the aforementioned existing technologies improve the overall structure. However, existing ternary copolymer polypropylene low-temperature toughening systems usually require the addition of a high proportion of elastomer to meet low-temperature impact requirements, resulting in a significant decrease in flexural modulus and heat distortion temperature. It is difficult to balance rigidity and toughness. Free β-crystal nucleating agents are randomly dispersed in the continuous polypropylene phase during melt blending and cannot be directionally enriched in the stress concentration area at the polypropylene / elastomer phase interface. They are also prone to agglomeration and migration, resulting in low nucleation efficiency and poor stability. Furthermore, the single-size elastic dispersed phase cannot simultaneously inhibit microcrack initiation and block crack propagation, and cannot form a graded energy dissipation mechanism during the increase of impact load. Summary of the Invention

[0003] The purpose of this invention is to provide a low-temperature high-impact ternary copolymer polypropylene modified material and its preparation method, in order to solve the problems mentioned in the background art. In order to achieve the low-temperature impact requirements, the ternary copolymer polypropylene low-temperature toughening system usually requires the addition of a high proportion of elastomer, which leads to a significant decrease in flexural modulus and heat distortion temperature. It is difficult to balance rigidity and toughness. The free β-crystal nucleating agent is randomly dispersed in the continuous polypropylene phase during melt blending and cannot be directionally enriched in the stress concentration area of ​​the polypropylene / elastomer phase interface. It is also prone to agglomeration and migration, resulting in low nucleation efficiency and poor stability. Furthermore, the single-size elastic dispersed phase cannot simultaneously inhibit microcrack initiation and block crack propagation, and cannot form a graded energy dissipation mechanism during the increase of impact load.

[0004] To achieve the above objectives, the present invention provides the following technical solution: a low-temperature, high-impact ternary copolymer polypropylene modified material, comprising, by weight: 70-82 parts of ternary copolymer polypropylene; 6-12 parts of ethylene-octene block copolymer; 3-8 parts of propylene-based elastomer; 3-7 parts of interface crystallization toughening masterbatch; 0.2-0.6 parts of antioxidant; 0.1-0.5 parts of lubricant; and 0.05-0.2 parts of acid absorbent; wherein the ternary copolymer polypropylene is a random copolymer of propylene, ethylene, and 1-butene; wherein the interface crystallization toughening masterbatch is prepared by melt reaction of maleic anhydride-grafted ethylene-octene block copolymer and an aromatic amide β-crystal nucleating agent containing bis-primary amino groups; wherein at least one primary amino group of the aromatic amide β-crystal nucleating agent forms an amide-acid bond and / or an imide bond with the maleic anhydride group of the maleic anhydride-grafted ethylene-octene block copolymer.

[0005] Furthermore, the terpolymer polypropylene contains 2.5% to 4.5% ethylene structural units, 1.2% to 3.2% 1-butene structural units, and the remainder is propylene structural units; the terpolymer polypropylene has a melt flow rate of 1.0 to 6.0 g / 10 min at 230°C and 2.16 kg.

[0006] Furthermore, the glass transition temperature of the ethylene-octene block copolymer is not higher than -50°C, and the melt flow rate at 190°C and 2.16 kg is 0.5–3.0 g / 10 min; the mass content of ethylene structural units in the propylene-based elastomer is 8%–18%, the glass transition temperature is not higher than -25°C, and the melt flow rate at 230°C and 2.16 kg is 3.0–10.0 g / 10 min.

[0007] Furthermore, the maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene block copolymer is 0.3% to 1.5%; the aromatic amide β-crystal nucleating agent containing two primary amino groups is N,N′-dicyclohexyl-1,5-diamino-2,6-naphthalenediamide, or an aromatic diamide compound containing two primary amino groups that can induce polypropylene to form a β-crystal.

[0008] Furthermore, when preparing the interface crystallization toughening masterbatch, the molar ratio of the primary amino group contained in the aromatic amide β-crystal nucleating agent to the maleic anhydride group contained in the maleic anhydride-grafted ethylene-octene block copolymer is 0.15:1 to 0.55:1; the gel content of the interface crystallization toughening masterbatch is not higher than 3%.

[0009] Furthermore, the modified material has a bimodal particle size distribution in its elastic dispersed phase, wherein the median particle size of the first elastic dispersed phase is 0.15–0.45 μm and the median particle size of the second elastic dispersed phase is 0.8–1.8 μm; the relative content of β crystals Kβ, as measured by wide-angle X-ray diffraction, is 0.20–0.55.

[0010] A method for preparing a low-temperature, high-impact ternary copolymer polypropylene modified material includes the following steps: S1: Maleic anhydride-grafted ethylene-octene block copolymer is melt-reacted with an aromatic amide β-crystal nucleating agent containing bis-primary amino groups to obtain interfacial crystallization toughening masterbatch; S2: Ternary copolymer polypropylene, ethylene-octene block copolymer, partially interfacial crystallization toughening masterbatch, antioxidant, lubricant and acid absorbent are added through the main feed port of the twin-screw extruder and subjected to upstream melt mixing; S3: The propylene-based elastomer and the remaining interfacial crystallization toughening masterbatch are added through the side feed port located in the middle and lower reaches of the twin-screw extruder and dispersed and mixed downstream. S4: The modified material is obtained by vacuum devolatilization, extrusion, cooling and granulation.

[0011] Furthermore, the melting reaction temperature of process S1 is 165–195°C, the screw speed is 120–260 r / min, the residence time is 45–120 s, and the reaction byproducts are removed under an absolute pressure of 10–40 kPa; the interface crystallization toughening masterbatch also includes 10–30 parts by weight of ternary copolymer polypropylene relative to 100 parts by weight of maleic anhydride-grafted ethylene-octene block copolymer.

[0012] Furthermore, in process S2, 50% to 75% of the total amount of the interface crystallization toughening masterbatch is added, and in process C, 25% to 50% of the total amount of the interface crystallization toughening masterbatch is added; the processing temperature of the twin-screw extruder is 165 to 205°C, the screw speed is 250 to 450 r / min, the material specific energy consumption is 0.15 to 0.35 kWh / kg, and the extrudate is cooled in water at 10 to 25°C.

[0013] Compared with the prior art, the beneficial effects of the present invention are: This low-temperature high-impact ternary copolymer polypropylene modified material and its preparation method fix β-crystal nucleating groups to maleic anhydride-grafted OBC segments through chemical bonds, reducing the proportion of random nucleation and aggregation of free nucleating agents in the continuous phase, and making the nucleation function more concentrated at the elastomer phase interface. Furthermore, the β-crystal enrichment region near the interface has a low crystal density and a high plastic deformation capacity, which can mitigate the modulus abrupt change between the continuous phase and the elastic phase of polypropylene, improve stress transmission stability, and promote shear yielding. Furthermore, the first elastic dispersed phase is used to provide high-density microcavities and prevent microcrack initiation, while the second elastic dispersed phase is used to induce cavitation under higher impact loads and induce large-scale matrix yielding. The two phases form a graded energy dissipation. Furthermore, under the same low-temperature impact target, the total amount of elastomer can be reduced, and the loss of flexural modulus and heat deformation performance caused by a large amount of POE or OBC can be reduced. Moreover, the entire preparation process is completed using conventional twin-screw extrusion equipment, without the need for dynamic vulcanization devices, nanofiller surface treatment or subsequent solvent cleaning, making it suitable for continuous production. Attached Figure Description

[0014] Figure 1 This is a schematic diagram of the overall process of the present invention; Figure 2 This is a detailed flowchart of step S1 of the present invention; Figure 3 This is a detailed flowchart of step S2 of the present invention. Figure 4 This is a detailed flowchart of steps S3 and S4 of the present invention. Detailed Implementation

[0015] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] Example 1: Please refer to Figures 1-4 This invention provides the following technical solution: a low-temperature, high-impact ternary copolymer polypropylene modified material. To address the problem that rigidity and toughness are difficult to balance, and that free β-crystal nucleating agents are randomly dispersed in the continuous polypropylene phase during melt blending, failing to directionally accumulate in the stress concentration region at the polypropylene / elastomer phase interface and thus unable to form a graded energy dissipation mechanism during increased impact load, the invention discloses, by weight, the following: 70 parts of ternary copolymer polypropylene: The ternary copolymer polypropylene is a random copolymer of propylene, ethylene and 1-butene. The ternary copolymer polypropylene has a mass content of 2.5% of ethylene structural units, a mass content of 1.2% of 1-butene structural units, and the remainder is propylene structural units. The melt flow rate of the ternary copolymer polypropylene at 230℃ and 2.16kg is 1.0g / 10min. 6 parts of ethylene-octene block copolymer: The ethylene-octene block copolymer has a glass transition temperature not higher than -50℃ and a melt flow rate of 0.5 g / 10 min at 190℃ and 2.16 kg; the propylene-based elastomer has an ethylene structural unit content of 8%, a glass transition temperature not higher than -25℃, and a melt flow rate of 3.0 g / 10 min at 230℃ and 2.16 kg. 3 parts of acrylic elastomer; 3 parts of interfacial crystallization toughening masterbatch: The interface crystallization toughening masterbatch is prepared by melt reaction of maleic anhydride-grafted ethylene-octene block copolymer and a β-crystal nucleating agent containing two primary amino groups. At least one primary amino group of the aromatic amide β-crystal nucleating agent forms an amide-acid bond and / or an imide bond with the maleic anhydride group of the maleic anhydride-grafted ethylene-octene block copolymer. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene block copolymer is 0.3%. The β-crystal nucleating agent containing two primary amino groups is N,N′-dicyclohexyl-1,5-diamino-2,6-naphthalenedicarboxamide, or an aromatic diamide compound containing two primary amino groups that can induce polypropylene to form a β-crystal. Antioxidant 0.2 parts; Lubricant 0.1 parts; Acid absorbent 0.05 parts; When preparing the interface crystallization toughening masterbatch, the molar ratio of the primary amino group in the aromatic amide β-crystal nucleating agent to the maleic anhydride group in the maleic anhydride-grafted ethylene-octene block copolymer is 0.15:1; the gel mass content of the interface crystallization toughening masterbatch is not higher than 3%; the elastic dispersed phase in the modified material has a bimodal particle size distribution, wherein the median volume particle size of the first elastic dispersed phase is 0.15 μm and the median volume particle size of the second elastic dispersed phase is 0.8 μm; the relative content of β crystals Kβ measured by wide-angle X-ray diffraction is 0.20.

[0017] One method for preparing a low-temperature, high-impact ternary copolymer polypropylene modified material includes the following steps: S1: Maleic anhydride-grafted ethylene-octene block copolymer is melt-reacted with an aromatic amide β-crystal nucleating agent containing bis-primary amino groups to obtain an interfacial crystallization toughening masterbatch. The melting reaction temperature of process S1 is 165℃, the screw speed is 120r / min, the residence time is 45s, and the reaction by-products are removed under an absolute pressure of 10kPa. The interfacial crystallization toughening masterbatch also includes 10 parts by weight of ternary copolymer polypropylene relative to 100 parts by weight of maleic anhydride-grafted ethylene-octene block copolymer. S2: Ternary copolymer polypropylene, ethylene-octene block copolymer, a portion of interfacial crystallization toughening masterbatch, antioxidant, lubricant, and acid absorbent are added through the main feed port of a twin-screw extruder and subjected to upstream melt mixing. 50% of the total amount of the interfacial crystallization toughening masterbatch is added in process S2, and 25% of the total amount of the interfacial crystallization toughening masterbatch is added in process C. The processing temperature of the twin-screw extruder is 165℃, the screw speed is 250r / min, the material specific energy consumption is 0.15kWh / kg, and the extrudate is cooled in water at 10℃. S3: The propylene-based elastomer and the remaining interfacial crystallization toughening masterbatch are added through the side feed port located in the middle and lower reaches of the twin-screw extruder and dispersed and mixed downstream. S4: The modified material is obtained by vacuum devolatilization, extrusion, cooling and granulation; By fixing the β-crystal nucleating groups to the maleic anhydride-grafted OBC segments through chemical bonds, the proportion of random nucleation and aggregation of free nucleating agents in the continuous phase is reduced, allowing the nucleation function to act more concentratedly on the elastomer phase interface. The β-crystal enrichment region near the interface has a lower crystal density and a higher plastic deformation capacity, which can slow down the modulus abrupt change between the continuous phase and the elastic phase of polypropylene, improve stress transmission stability, and promote shear yielding.

[0018] Example 2: Based on Example 1, the following differences are further disclosed, as detailed below: By weight, it includes: 75 parts of ternary copolymer polypropylene: The ternary copolymer polypropylene is a random copolymer of propylene, ethylene and 1-butene. The ternary copolymer polypropylene has a mass content of 3.5% of ethylene structural units, a mass content of 2% of 1-butene structural units, and the remainder is propylene structural units. The melt flow rate of the ternary copolymer polypropylene at 230℃ and 2.16kg is 4.0g / 10min. 6-12 parts of ethylene-octene block copolymer: The ethylene-octene block copolymer has a glass transition temperature not higher than -50℃ and a melt flow rate of 2 g / 10 min at 190℃ and 2.16 kg; the propylene-based elastomer has an ethylene structural unit content of 12%, a glass transition temperature not higher than -25℃, and a melt flow rate of 6 g / 10 min at 230℃ and 2.16 kg. 5 parts of acrylic elastomer; 5 parts of interfacial crystallization toughening masterbatch: The interface crystallization toughening masterbatch is prepared by melt reaction of maleic anhydride-grafted ethylene-octene block copolymer and a β-crystal nucleating agent containing two primary amino groups. At least one primary amino group of the aromatic amide β-crystal nucleating agent forms an amide-acid bond and / or an imide bond with the maleic anhydride group of the maleic anhydride-grafted ethylene-octene block copolymer. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene block copolymer is 1%. The β-crystal nucleating agent containing two primary amino groups is N,N′-dicyclohexyl-1,5-diamino-2,6-naphthalenedicarboxamide, or an aromatic diamide compound containing two primary amino groups that can induce polypropylene to form a β-crystal. Antioxidant 0.35 parts; Lubricant 0.25 parts; Acid absorbent 0.1 parts; When preparing the interface crystallization toughening masterbatch, the molar ratio of the primary amino group in the aromatic amide β-crystal nucleating agent to the maleic anhydride group in the maleic anhydride-grafted ethylene-octene block copolymer is 0.35:1; the gel mass content of the interface crystallization toughening masterbatch is not higher than 3%; the elastic dispersed phase in the modified material has a bimodal particle size distribution, wherein the median volume particle size of the first elastic dispersed phase is 0.25 μm and the median volume particle size of the second elastic dispersed phase is 1.2 μm; the relative content of β crystals Kβ measured by wide-angle X-ray diffraction is 0.35.

[0019] One method for preparing a low-temperature, high-impact ternary copolymer polypropylene modified material includes the following steps: S1: Maleic anhydride-grafted ethylene-octene block copolymer is melt-reacted with an aromatic amide β-crystal nucleating agent containing bis-primary amino groups to obtain an interfacial crystallization toughening masterbatch. The melting reaction temperature of process S1 is 180℃, the screw speed is 200r / min, the residence time is 80s, and the reaction by-products are removed under an absolute pressure of 25kPa. The interfacial crystallization toughening masterbatch also includes 15 parts by weight of ternary copolymer polypropylene relative to 100 parts by weight of maleic anhydride-grafted ethylene-octene block copolymer. S2: Ternary copolymer polypropylene, ethylene-octene block copolymer, a portion of interfacial crystallization toughening masterbatch, antioxidant, lubricant, and acid absorbent are added through the main feed port of a twin-screw extruder and subjected to upstream melt mixing. 60% of the total amount of the interfacial crystallization toughening masterbatch is added in process S2, and 35% of the total amount is added in process C. The processing temperature of the twin-screw extruder is 180℃, the screw speed is 350 r / min, the material specific energy consumption is 0.25 kWh / kg, and the extrudate is cooled in water at 15℃. S3: The propylene-based elastomer and the remaining interfacial crystallization toughening masterbatch are added through the side feed port located in the middle and lower reaches of the twin-screw extruder and dispersed and mixed downstream. S4: The modified material is obtained by vacuum devolatilization, extrusion, cooling and granulation.

[0020] Example 3: Based on Examples 1 and 2, the following differences are also disclosed, as detailed below: By weight, it includes: 82 parts of ternary copolymer polypropylene: The ternary copolymer polypropylene is a random copolymer of propylene, ethylene and 1-butene. The ternary copolymer polypropylene has a mass content of 4.5% of ethylene structural units, a mass content of 3.2% of 1-butene structural units, and the remainder is propylene structural units. The melt mass flow rate of the ternary copolymer polypropylene at 230℃ and 2.16kg is 6.0g / 10min. 6-12 parts of ethylene-octene block copolymer: The ethylene-octene block copolymer has a glass transition temperature not higher than -50℃ and a melt flow rate of 3.0 g / 10 min at 190℃ and 2.16 kg; the propylene-based elastomer has an ethylene structural unit content of 18%, a glass transition temperature not higher than -25℃, and a melt flow rate of 10.0 g / 10 min at 230℃ and 2.16 kg. 8 parts of propylene-based elastomer; 7 parts of interfacial crystallization toughening masterbatch: The interface crystallization toughening masterbatch is prepared by melt reaction of maleic anhydride-grafted ethylene-octene block copolymer and a β-crystal nucleating agent containing two primary amino groups. At least one primary amino group of the aromatic amide β-crystal nucleating agent forms an amide-acid bond and / or an imide bond with the maleic anhydride group of the maleic anhydride-grafted ethylene-octene block copolymer. The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene block copolymer is 1.5%. The β-crystal nucleating agent containing two primary amino groups is N,N′-dicyclohexyl-1,5-diamino-2,6-naphthalenedicarboxamide, or an aromatic diamide compound containing two primary amino groups that can induce polypropylene to form a β-crystal. Antioxidant 0.6 parts; Lubricant 0.5 parts; Acid absorbent 0.2 parts; When preparing the interface crystallization toughening masterbatch, the molar ratio of the primary amino group in the aromatic amide β-crystal nucleating agent to the maleic anhydride group in the maleic anhydride-grafted ethylene-octene block copolymer is 0.55:1; the gel mass content of the interface crystallization toughening masterbatch is not higher than 3%; the elastic dispersed phase in the modified material has a bimodal particle size distribution, wherein the median volume particle size of the first elastic dispersed phase is 0.45 μm and the median volume particle size of the second elastic dispersed phase is 1.8 μm; the relative content of β crystals Kβ measured by wide-angle X-ray diffraction is 0.55.

[0021] One method for preparing a low-temperature, high-impact ternary copolymer polypropylene modified material includes the following steps: S1: Maleic anhydride-grafted ethylene-octene block copolymer is melt-reacted with an aromatic amide β-crystal nucleating agent containing bis-primary amino groups to obtain an interfacial crystallization toughening masterbatch. The melting reaction temperature of process S1 is 195℃, the screw speed is 260r / min, the residence time is 120s, and the reaction by-products are removed under an absolute pressure of 40kPa. The interfacial crystallization toughening masterbatch also includes 30 parts by weight of ternary copolymer polypropylene relative to 100 parts by weight of maleic anhydride-grafted ethylene-octene block copolymer. S2: Ternary copolymer polypropylene, ethylene-octene block copolymer, a portion of interfacial crystallization toughening masterbatch, antioxidant, lubricant, and acid absorbent are added through the main feed port of a twin-screw extruder and subjected to upstream melt mixing. 75% of the total amount of the interfacial crystallization toughening masterbatch is added in process S2, and 50% of the total amount is added in process C. The processing temperature of the twin-screw extruder is 205℃, the screw speed is 450 r / min, the material specific energy consumption is 0.35 kWh / kg, and the extrudate is cooled in water at 25℃. S3: The propylene-based elastomer and the remaining interfacial crystallization toughening masterbatch are added through the side feed port located in the middle and lower reaches of the twin-screw extruder and dispersed and mixed downstream. S4: The modified material is obtained by vacuum devolatilization, extrusion, cooling and granulation; While free BN-R can induce certain β crystals, its random dispersion within the continuous phase makes it prone to aggregation and unable to continuously cover the newly formed elastic interface. Reaction-fixed BN-R preferentially reaches the phase interface along with OBC segments, improving plastic deformation near the interface with a lower total nucleating agent amount. Non-reactive carrier masterbatches cannot prevent the migration of nucleating agents during melt shearing and subsequent use, and the spatial correlation between nucleating agents and the elastic phase is weak. Therefore, its low-temperature impact gain and performance stability are lower than those of reaction-fixed masterbatches. Single-feeding causes OBC and PBE to undergo similar shear processes, making it difficult to stably form a bimodal dispersed phase. Segmented feeding allows small-particle-size and large-particle-size phases to have different cavitation thresholds, sequentially activating energy-consuming mechanisms during impact load increases. When the BN-R dosage or primary amino / maleic anhydride molar ratio is too high, inter-chain coupling and gelation may occur in the masterbatch, leading to decreased flowability. When the dosage is too low, interfacial β crystal induction is insufficient. Therefore, masterbatch gel content, free nucleating agent ratio, Kβ, and low-temperature impact strength should be used together as process window evaluation indicators.

[0022] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "connected" and "linked" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.

[0023] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A low-temperature, high-impact ternary copolymer polypropylene modified material, characterized in that, By weight, it includes: 70-82 parts of ternary copolymer polypropylene; 6-12 parts of ethylene-octene block copolymer; 3-8 parts of propylene-based elastomer; 3-7 parts of interfacial crystallization toughening masterbatch; 0.2-0.6 parts of antioxidant; 0.1-0.5 parts of lubricant and 0.05-0.2 parts of acid absorbent; The ternary copolymer polypropylene is a random copolymer of propylene, ethylene and 1-butene; The interface crystallization toughening masterbatch is prepared by melting reaction of maleic anhydride-grafted ethylene-octene block copolymer and aromatic amide β-crystal nucleating agent containing bis-primary amino groups. At least one primary amino group of the aromatic amide β-crystal nucleating agent forms an amide bond and / or an imide bond with the maleic anhydride group of the maleic anhydride-grafted ethylene-octene block copolymer.

2. The low-temperature high-impact ternary copolymer polypropylene modified material according to claim 1, characterized in that: The ternary copolymer polypropylene contains 2.5% to 4.5% ethylene structural units, 1.2% to 3.2% 1-butene structural units, and the remainder is propylene structural units. The melt flow rate of the ternary copolymer polypropylene at 230℃ and 2.16kg is 1.0~6.0g / 10min.

3. The low-temperature high-impact ternary copolymer polypropylene modified material according to claim 2, characterized in that: The glass transition temperature of the ethylene-octene block copolymer is not higher than -50°C, and the melt mass flow rate at 190°C and 2.16 kg is 0.5 to 3.0 g / 10 min. The propylene-based elastomer has an ethylene structural unit content of 8% to 18%, a glass transition temperature not higher than -25°C, and a melt mass flow rate of 3.0 to 10.0 g / 10 min at 230°C and 2.16 kg.

4. The low-temperature high-impact ternary copolymer polypropylene modified material according to claim 3, characterized in that: The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene block copolymer is 0.3% to 1.5%. The nucleating agent for the β-crystal form of the aromatic amide containing two primary amino groups is N,N′-dicyclohexyl-1,5-diamino-2,6-naphthalenediamide, or an aromatic diamide compound containing two primary amino groups that can induce polypropylene to form a β-crystal form.

5. The low-temperature high-impact ternary copolymer polypropylene modified material according to claim 4, characterized in that: When preparing the interface crystallization toughening masterbatch, the molar ratio of the primary amino group contained in the aromatic amide β-crystal nucleating agent to the maleic anhydride group contained in the maleic anhydride-grafted ethylene-octene block copolymer is 0.15:1 to 0.55:1; The gel content of the interface crystallization toughening masterbatch is no higher than 3%.

6. The low-temperature high-impact ternary copolymer polypropylene modified material according to claim 5, characterized in that: The modified material has a bimodal particle size distribution in its elastic dispersed phase, wherein the median volumetric particle size of the first elastic dispersed phase is 0.15–0.45 μm and the median volumetric particle size of the second elastic dispersed phase is 0.8–1.8 μm; the relative content of β crystals Kβ, as measured by wide-angle X-ray diffraction, is 0.20–0.

55.

7. A method for preparing a low-temperature high-impact ternary copolymer polypropylene modified material, which is applied to the preparation of a low-temperature high-impact ternary copolymer polypropylene modified material as described in any one of claims 1-6, characterized in that, The process includes the following: S1: Maleic anhydride-grafted ethylene-octene block copolymer is melt-reacted with an aromatic amide β-crystal nucleating agent containing bis-primary amino groups to obtain interfacial crystallization toughening masterbatch; S2: Ternary copolymer polypropylene, ethylene-octene block copolymer, partially interfacial crystallization toughening masterbatch, antioxidant, lubricant and acid absorbent are added through the main feed port of the twin-screw extruder and subjected to upstream melt mixing; S3: The propylene-based elastomer and the remaining interfacial crystallization toughening masterbatch are added through the side feed port located in the middle and lower reaches of the twin-screw extruder and dispersed and mixed downstream. S4: The modified material is obtained by vacuum devolatilization, extrusion, cooling and granulation.

8. The method for preparing a low-temperature high-impact ternary copolymer polypropylene modified material according to claim 7, characterized in that: The melting reaction temperature of process S1 is 165-195℃, the screw speed is 120-260 r / min, the residence time is 45-120 s, and the reaction by-products are removed under an absolute pressure of 10-40 kPa; the interface crystallization toughening masterbatch also includes 10-30 parts by weight of ternary copolymer polypropylene relative to 100 parts by weight of maleic anhydride-grafted ethylene-octene block copolymer.

9. The method for preparing a low-temperature high-impact ternary copolymer polypropylene modified material according to claim 8, characterized in that: In process S2, 50% to 75% of the total amount of the interface crystallization toughening masterbatch is added, and in process C, 25% to 50% of the total amount of the interface crystallization toughening masterbatch is added; the processing temperature of the twin-screw extruder is 165 to 205°C, the screw speed is 250 to 450 r / min, the material specific energy consumption is 0.15 to 0.35 kWh / kg, and the extrudate is cooled in water at 10 to 25°C.

Citation Information

Patent Citations

  • Polypropylene modified ternary composite for plastic geogrid and preparation method and application

    CN105694228A

  • Polypropylene-ethylene propylene diene monomer modified composite material for automobile

    CN111073146A

  • A modified polypropylene material, its preparation method and use

    CN119661943B